Training on the Use of Interactive Digital Media for Arabic Language Learning at Darul Huda Islamic Boarding School, Wonodadi, Blitar - Moh Ikhsani; Anis Zunaidah; Choiruddin Choiruddin; Hanik Shofa Mardiyah; Imro’atus Sholikah (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose: Arabic language learning at Darul Huda Islamic Boarding School has traditionally relied on lectures, memorization, and written exercises. To modernize this approach, this mentoring program focused on improving teachers' capacity to utilize interactive digital media, specifically through training on applications like Quizizz, Wordwall, and Liveworksheets. Method: The program employed the Participatory Action Research (PAR) method, which involved collaborative stages of joint problem identification, action planning, implementation, evaluation, and reflective learning with the participating teachers. Practical Applications: The training enabled direct application in the classroom. Teachers can now use the digital tools to create interactive quizzes, vocabulary exercises, and self-grading assignments, making the learning process more engaging and efficient for both instructors and students. Conclusion: The integration of digital media has positively transformed Arabic language learning. Students have become more active and enthusiastic, with lessons gaining variety through games and instant feedback. Furthermore, the evaluation of learning outcomes has become significantly faster, more objective, and easier for teachers to manage.